Improving urban middle schools : lessons from the Nativity schools - Fenzel, L. Mickey, 1949- (State University of New York Press, 2009)
"L. Mickey Fenzel visited eleven Nativity schools in seven cities, conducting interviews and classroom observations, and collecting standardized test scores and survey data. Fenzel examines features of the Nativity model that distinguish it from other educational programs and takes a close look at the controversial use of volunteer teachers. The Nativity model is also discussed with respect to its social justice mission that is rooted in the Jesuit tradition."--BOOK JACKET.